Exports Driven by Hallyu Increasing South Korea’s Economic Growth - Cultural Diplomacy Approach - titing reza reza (Jurnal Hubungan Internasional, 2022)
Hallyu, or what was known as the Korean Wave that expanded through globalisation, was used as a soft power instrument for South Korean cultural Diplomacy to repair South Korean relations with other countries, as well as to develop its economic sites. Hallyu products can increase South Korea’s GDP by 0.2% in 2004 or by $ 1.87 billion, and it even reached $12.3 in 2019. This study uses four variables of Hallyu products that drive Korean economics: Cosmetics or K-beauty, Fashions, Inbound Tourism and education, compared with the other four highest non-Hallyu variables such as Electrical, Nuclear, Vehicles and Plastics. By using the correlations analysis method with python, the mathematical model of finding shows that the correlation of Hallyu products to South Korea’s GDP per capita was robust, even reaching a positive number of 0.89 compared to non-Hallyu products with a positive value of 0.44. This circumstance indicates that the Hallyu product has a very high correlation, where there was a positive increase of a fixed proportion in the other. Therefore, cultural Diplomacy carried out by South Korea was an example of soft power that has succeeded in controlling not only diplomacy but the economy as well.